THE EFFECT OF WORK ENVIRONMENT AND HUMAN RESOURCE EMPOWERMENT ON EMPLOYEE JOB SATISFACTION WITH TRAINING AS A MEDIATION VARIABLE AT THE DEPARTMENT OF HUMAN RURAL WORKS AND CONSTRUCTION BUILDING OF NORTH SUMATERA PROVINCE - Shafira Husna, An Nura; Aditi, Bunga; Nahrisah, Ezzah (Berajah Journal, 2024)
This study aims to determine the influence of the work environment and human resource empowerment on training partially. To analyze the influence of the work environment, human resource empowerment and training on employee job satisfaction partially. To analyze the influence of the work environment and human resource empowerment on employee job satisfaction through training at the Department of Highways and Construction of North Sumatra Province. The population in this study was 446 people and 234 people were sampled using the Slovin formula. The analysis technique used was path analysis. The results of the study indicate that the work environment has a positive and significant effect on training, human resource empowerment does not affect training, the work environment affects employee job satisfaction, human resource empowerment affects employee job satisfaction, training has a positive and significant effect on employee job satisfaction, training mediates the effect of the work environment on employee job satisfaction and training does not mediate the effect of human resource empowerment on employee job satisfaction.